Systems of Systems (SoS) meta‐architecture evaluation utilizing the SoS Explorer for cyber‐physical smart solar roadways. (13th September 2022) - Schaefer, Thomas; Dagli, Cihan H
Abstract: Smart solar roadways are an emerging cyber‐physical technology being developed by companies worldwide with some roadways even being in the early stages of implementation. These roadway systems have complex capabilities and connections with other systems. The recent and continuous advancements in solar technologies and wireless data transfer there exists a need to be able to evaluate the system of systems meta‐architecture for the development and implementation of smart solar roadways. Therefore, this paper outlines an example of the possibility for evaluation of the meta‐architectures using fuzzy logic assessors and genetic algorithms in conjunction with the SoS Explorer Application developed by the Engineering Management and Systems Engineering Department of Missouri University of Science and Technology. The optimal solution for the smart solar roadway maximizes each of the Key Performance Attributes (KPA) Affordability, Availability, Durability and Responsiveness. The KPAs can be assessed in a Fuzzy Inference System (FIS) to assess the fitness measure of the optimum SoS meta‐architecture generated by the genetic algorithm. The SoS Explorer Application is used to visualize the selected SoS meta‐architecture as a chromosome. Using this approach will allow local governments to make the optimal selection of systems to develop a smart solar roadway even as technology continues to progress.